Development of a Language Tourism Village Based on Environmental Ethics and Social Entrepreneurship (A Case Study in Karanganyar Regency, Central Java, Indonesia) - Wibowo Agung (EDP Sciences, 2021)
Numerous environmental problems have emerged along with the development of tourism villages in various areas of Indonesia. This research aims to discover a concept of sustainable tourism village development, and to describe principles of environmental ethics and social entrepreneurship that are line with global demands. The research uses a qualitative method. The location of the research is the District of Karangpandan in Karanganyar Regency, the first language tourism village in Central Java. Data sources include both primary and secondary data. The data collection techniques were interviews, observation, and documentation. The data analysis included the stages of data collection, data reduction, data presentation, and conclusion. The research results show that the model of developing a language tourism village based on the principles of environmental ethics and social entrepreneurship has been proven to contribute to the success of developing village tourism. The principles of environmental ethics consist of respect for nature, moral responsibility for nature, cosmic solidarity, principle of care and concern for nature, principle of “no harm”, principle of living simply and in harmony with nature, principle of justice the principles of environmental ethics inspire stakeholders in preserving the environment. Furthermore, the components of social entrepreneurship include: resources, networking, research and development, packaging, marketing, and branding, Leadership and Entrepreneurship and all that gives inspiration for empowering the surrounding community.